Progressive Encephalomyelitis With Rigidity and Myoclonus With Thymoma: A Case Report and Literature Review - Su, Yana; Cui, Li; Zhu, Mingqin; Liang, Yixuan; Zhang, Ying (Frontiers in Neurology, 2020)
Progressive encephalomyelitis with rigidity and myoclonus (PERM) is part of the variant type of the Stiff Person Syndrome (SPS) and is a rare neurological disease. We report here a patient with PERM who had thymoma and was positive for anti-glutamic acid decarboxylase (anti-GAD) antibodies. Her symptoms improved after treatment with hormones and gamma globulin. We also summarized the literature review of patients with PERM accompanied by tumors reported.